The Wesleyan Synthesis Reconsidered - Snyder, Howard A. (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
This article purpose finds what is “the Wesleyan synthesis,” and will also briefly revisit the much-discussed Wesleyan Quadrilateral. Wesley effectively combined in thought and practice these five elements, namely: (1) Divine sovereignty and human freedom, (2) Doctrine and experience, (3) Experience and structure, (4) Charismatic and institutional elements, and (5) Present and future salvation. This article argues that this synthesis is powerful, but also that it is biblical. In fact, the reason this synthesis is powerful is that it faithfully embodies the revealed truth of Scripture. The results of the Wesleyan synthesis are drawing three general conclusions. First, Wesley's theology was broader and more profound than has often been realized. Second, Wesley's theology can help us develop a biblical understanding of culture and culture change. Third, Wesley's theology is thus an open invitation to continue to develop a theology of church, mission, and culture that is profoundly biblical and sharply relevant to the present age.